Risk of neonatal hypothyroidism in newborns from mothers exposed to CTPA during pregnancy: Ancillary data from a prospective outcome study. (28th August 2022) - Righini, Marc; Robert‐Ebadi, Helia; Cremonesi, Alessio; Elias, Antoine; Sanchez, Olivier; Le Moigne, Emmanuelle; Schmidt, Jeannot; Le Gall, Catherine; Cornuz, Jacques; Aujesky, Drahomir; Roy, Pierre‐Marie; Chauleur, Céline; et al.
Abstract: Background: Neonatal hypothyroidism is often raised as a potential concern for the use of computed tomography pulmonary angiography (CTPA) in pregnant women with suspected pulmonary embolism (PE). Objectives: To assess the incidence of neonatal hypothyroidism among newborns from mothers exposed to CTPA. Patients/Methods: Pregnant women with clinically suspected PE were included in a multicenter, multinational prospective diagnostic management outcome study, based on pretest clinical probability assessment, high‐sensitivity D‐dimer testing, bilateral lower limb venous compression ultrasonography, and CTPA. Results of Guthrie tests were systematically collected for newborns of all women who required CTPA as part of the diagnostic strategy. A thyroid‐stimulating hormone (TSH) level above 15 U/ml was used to define hypothyroidism. Results: Out of the 166 women included in the Swiss participating centers, 149 underwent a CTPA including 14 with twin pregnancies. Eight women suffered a pregnancy loss and results of the Guthrie test could not be retrieved for four newborns. All TSH levels were reported as being below 15 U/ml. The incidence of neonatal hypothyroidism was 0/151 (0.0%, 95% confidence interval: 0.0%–2.5%). Conclusions: We did not identify any cases of neonatal hypothyroidism in our cohort of 149 pregnant women investigated for suspected PE using a CTPA. Along with previous literature data, this provides further reassuring data regarding the use of CTPA in this indication.